High-speed railways : environmental impact and pollution prevention and control - He, Yulong; Tao, Wei (Of Sichuan li gong xue yuan); Mei, Changgen (Elsevier, 2023)
"High-Speed Railways: Environmental Impact and Pollution Prevention and Control considers environmental pollution and pollution control technology in the construction and operation of high-speed rail infrastructure. In six chapters, this new volume introduces high speed rail and environmental impact, considers environmental pollution and prevention in high speed railways, and covers the prediction, measurement and prevention of key environmental aspects of the railway. The title gives engineers the means to understand and mitigrate the
Keywords: High speed trains -- Environmental aspects.; elektronické knihy; electronic books